2020
DOI: 10.1111/jsr.13216
|View full text |Cite
|
Sign up to set email alerts
|

PTPRD as a candidate druggable target for therapies for restless legs syndrome?

Abstract: The gene that encodes the protein tyrosine phosphatase D (PTPRD) may be related to brain circuits associated with sleep, and has been seen as an interesting molecule, a “druggable” drug target. This gene is a potential candidate for increasing therapeutic advances in restless legs syndrome, a sleep‐related movement disorder, that manifests as an uncontrollable desire to move limbs (legs) to relieve uncomfortable sensations. Changes in the PTPRD gene expression may increase the chance of developing this syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The second exercise increased PTPRD (protein tyrosine phosphatase receptor delta-type) protein levels, decreased tyrosine hydroxylase (TH) protein levels and improved sleep parameters in both cycles of restless leg syndrome. The results of this study showed an improvement in sleep parameters in both cycles of restless leg syndrome (Wang et al, 2022) (Morais et al, 2023). However, one study showed that excessively strenuous physical activity disrupts redox homeostasis against oxidative stress (Kruk et al, 2019), which disrupts the antioxidant status of the body and thus affects sleep quality.…”
Section: Declarationsmentioning
confidence: 71%
See 1 more Smart Citation
“…The second exercise increased PTPRD (protein tyrosine phosphatase receptor delta-type) protein levels, decreased tyrosine hydroxylase (TH) protein levels and improved sleep parameters in both cycles of restless leg syndrome. The results of this study showed an improvement in sleep parameters in both cycles of restless leg syndrome (Wang et al, 2022) (Morais et al, 2023). However, one study showed that excessively strenuous physical activity disrupts redox homeostasis against oxidative stress (Kruk et al, 2019), which disrupts the antioxidant status of the body and thus affects sleep quality.…”
Section: Declarationsmentioning
confidence: 71%
“…For instance, physical activity has been proven to be bene cial for MCI and dementia (Nuzum et al, 2020). In addition, functional recovery in patients with bidirectional depression (Hamada et al, 2023), neuroendocrine abnormalities in Parkinson's disease (Luthra et al, 2023), restless leg syndrome(RLS) (Morais et al, 2023), have all demonstrated improvement. However, research on exercise and sleep disorders in middle-aged adults is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the effects of iron deficiency on the spinal dopamine system and brain have suggested that adenosine may play an important role in the disease. Clinical and animal studies have demonstrated a putative link between RLS risk alleles and iron [ 69 ] and basal ganglia development. [ 29 ] Despite the remarkable convergence phenomena,…”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…Some research has explored the PTPRD in RLS animals models (Drgonova et al, 2015; Morais et al, 2020; Uhl & Martinez, 2019; Yin et al, 2012); however, still it has not been demonstrated the sequencing of the PTPRD gene in the SHR and WK strains. Morais et al (2020) observed that the use of pramipexole in SHRs may alter PTPRD protein content in the spinal cord; however, that study did not analyse the baseline levels of PTPRD compared to another strain that does not develop RLS.…”
Section: Discussionmentioning
confidence: 99%